Adherence to treatment guidelines in Type 2 diabetes patients failing metformin monotherapy in a real-world setting. (January 2015) - Tunceli, Kaan; Goldshtein, Inbal; Yu, Shengsheng; Sharon, Ofer; Brodovicz, Kimberly; Gadir, Noga; Katzeff, Harvey; Voss, Bernd; Radican, Larry; Chodick, Gabriel; Shalev, Varda; Maor, Yasmin; et al.
SUMMARY : Aim: To describe the drug management of T2DM patients in a real life cohort with suboptimal HbA1c after treatment with metformin monotherapy.Methods: we performed a retrospective cohort analysis of computerized medical records after measuring an HbA1c >7% for the first time following at least 90 days on metformin therapy.Results: Among 7705 eligible patients, 56% (n = 4336) changed treatment within 1-year, by increasing metformin dose (36%), adding drugs (60%), or switching to other medications (4%). Strongest predictors of change were higher HbA1c, younger age and higher socioeconomic status (SES).Conclusion: In this cohort, the extent of inertia appears to be smaller than that reported in previous studies. Nonetheless, disease management programs aimed at improving guideline adherence and reducing inertia are still warranted.